An Advanced Motion Vectors Using Sensitive Video Steganography - S. , Senthilkumar; V. , Amirthalingam; R. , Bharanidharan; M. , Vimal Gautham (International Journal of Psychosocial Rehabilitation, 2020)
Video steganography is considered a technique for concealing data, and mystery correspondence of the most noteworthy issues that happened in the protected information transmission in the electronic age. The video steganography plot dependent on motion vectors and straight square codes has been proposed in this paper. Our technique implants mystery messages in the motion vectors of spread media during the procedure of H.264 packing. Linear block codes have been used to lessen the alteration pace of the motion vectors. In this paper, an advanced motion vector-based video steganography technique is proposed. For embedding the mystery bit stream, the embedding motion vectors are chosen for the homogeneous districts of the reference outline. Since homogeneous or smooth locales contain full-scale obstructs with comparative expectation blunder squares, it assists with lessening the opportunity of discovery by concealing the embedding clamor with comparative forecast mistakes among neighboring large-scale squares. The proficient inquiry window and polar direction-based embedding strategy are utilized to improve the intangibility against standard steganalysis plans. A lot of examinations have been completed to legitimize the viability of the proposed conspiracy over the related existing steganographic strategies.